Liver Cirrhosis as a Risk Factor for Direct-Acting Antiviral Therapy Failure in Real-Life Hepatitis C Virus/Human Immunodeficiency Virus Coinfection. (27th July 2017) - Boesecke, Christoph; Ingiliz, Patrick; Berger, Florian; Lutz, Thomas; Schewe, Knud; Schulze zur Wiesch, Julian; Baumgarten, Axel; Christensen, Stefan; Rockstroh, Jürgen K; Mauss, Stefan; ,
Abstract: Current hepatitis C virus (HCV) treatment guidelines recommend treating HCV/human immunodeficiency virus (HIV)-coinfected individuals similar to HCV-monoinfected individuals. Recently inferior response rates to direct acting antiviral (DAA) therapy in HCV/HIV coinfection have been reported. Our German hepatitis C cohort (GECCO) cohort data show that coinfected patients with liver cirrhosis are less likely to achieve viral eradication.